Dropout of Vaccination Among Iraqi Children - Kadim, Maha. A.; Abdulhasan, Anees Flayyih; Abdulrasol, Zainab Abdulameer; Obaid, Ali Fadhil (South Asian Journal of Social Sciences and Humanities, 2022)
Immunization has been a successful method of preventing and controlling life-threatening infectious diseases since the 20th century. About 2-3 million child deaths are avoided annually through vaccination. Despite increasing vaccination rates worldwide, many children in developing nations still miss their vaccinations. Therefore, many children are still vulnerable to the Expanded Program on Immunization (EPI) targeted diseases. Missed opportunities for vaccination (MOVs) occur when people who are eligible for vaccination visit a medical facility but do not receive the necessary vaccinations. Therefore, vaccination has the opportunity to achieve more if missed vaccination opportunities (MOVs) are removed and global immunization coverage increases. A narrative review was conducted to summarize vaccination missing among Iraqi children, and factors affecting the vaccine coverage rate.